(untitled) (The International Journal for Scientific Research, 2025)
Carex L. Sect. Trachychlaenae, Subgenus Carex viz. Carex hispida Willd. ex Schkuhr is a native taxon of the Mediterranean basin, and this is the first time it has been found in Libyan territory. It grew in a small swamp about 50 km west of Derna city. The records date from March 2017 to March 2022. Collecting this taxon from this area in east Libya, expands the known geographical distribution of Carex hispida and underscores the importance of continued botanical exploration across all regions.